2022
DOI: 10.1111/add.15843
|View full text |Cite
|
Sign up to set email alerts
|

Problematic gaming risk among European adolescents: a cross‐national evaluation of individual and socio‐economic factors

Abstract: Table S2. Prevalence of low (0-1) and high (2-3) risk of Problematic Gaming, stratified by country and gender, 2019.Table S3. Individual-level variables included in the model (except gender): questions, rating system and computation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 57 publications
1
7
0
Order By: Relevance
“…These studies have shown that animals in lower hierarchical positions or with restricted access to resources exhibit higher levels of stress and are more prone to engage in drug-seeking behaviors. This mirrors findings in human populations, where individuals facing economic hardship and social marginalization are at a higher risk for developing addiction [59,60].…”
Section: Economic and Social Inequality Addiction Risk Factorssupporting
confidence: 74%
“…These studies have shown that animals in lower hierarchical positions or with restricted access to resources exhibit higher levels of stress and are more prone to engage in drug-seeking behaviors. This mirrors findings in human populations, where individuals facing economic hardship and social marginalization are at a higher risk for developing addiction [59,60].…”
Section: Economic and Social Inequality Addiction Risk Factorssupporting
confidence: 74%
“…The influence of the family is a pivotal factor, as it contributes significantly to the socialization of adolescents (Liu et al, 2015). Parental regulation through restrictive mediation or conversational mediation in adolescents' gaming is one important factor that may limit adolescents' gaming behavior (Colasante et al, 2022).…”
Section: Suggestions For Parents and College Managementmentioning
confidence: 99%
“…The emerging research has examined correlates of problem gaming in ways that make it difficult to determine the direct contribution of problem gaming or gaming behaviours to experienced harms. For example, cross-sectional studies of problem gaming and family-related factors ( Colasante et al., 2022 ; Schneider, King, & Delfabbro, 2017 ) have reported that adolescent GD is associated with a poorer parent-child relationship and a poorer family environment ( Charlie, HyeKyung, & Khoo, 2011 ; Kwon, Chung, & Lee, 2011 ; Liau et al, 2015 ; Rikkers, Lawrence, Hafekost, & Zubrick, 2016 ; Wang et al., 2014 ). However, it is usually not clear whether these issues were a precursor or a consequence (or both) of problem gaming.…”
Section: Introductionmentioning
confidence: 99%